Battlefield tourism - Akbulut, Onur; Ekin, Yakin; Güler, Mehmet Emre; Saribaş, Özgür (Tourism security-safety and post conflict destinations., 2024)
War and conflict have always been a recurring aspect of human history with a considerable impact on the countries involved, the formation of communities, and the global regulations. Battlefield Tourism offers a holistic approach to tourism in locations affected by conflict, an underdeveloped area of research in the tourism and hospitality sector. Using Leiper's tourism system model, the authors examine battlefield tourism in terms of the demand, supply, intermediaries, supporting institutions, and tourist flows. The chapters comprise of a range of perspectives on different elements of battlefield tourism, including topics such as Special Interest Tourism, Tourism Development, Stakeholders, Sustainability, Marketing, and Reenactment. Introducing real-world case studies from across the globe, Battlefield Tourism contributes to the growing fields of dark tourism, destination and risk management, and tourism security. The Tourism Security-Safety and Post Conflict Destinations series provides an insightful guide for policy makers, specialists and social scientists interested in the future of tourism in a society where uncertainness, anxiety and fear prevail.